Check-In Check-Out Behavior Support in Mainstream Schools: Intervention Response and Moderators. - Paananen, Mika; Karhu, Anne; Tolvanen, Asko; Savolainen, Hannu (Behavioral Disorders, 2026)
Check-In Check-Out (CICO) is a widely used intervention for students who need more intensive behavior support in school. Although CICO support has been extensively studied, there is still a lack of large-scale studies on the effectiveness of the CICO support as well as studies of moderators of the intervention effect. In this study, we evaluated the outcomes of the CICO support in Finnish schools and the effects of different moderators on behavioral change. Fifty-one students participated in the study. Positive and problem behaviors of the participating students were followed before, during and after CICO support. Moderating variables were individual-level factors. At the group level, the effect sizes for change in behavior were large. Individual-level factors were not connected to changes in behaviors. CICO support appeared effective across all grade levels, regardless of the pupil's need for pedagogical support, behavioral diagnosis, or preintervention problem behavior level.